IMPACT TESTING OF ORDNANCE GELATINE UNDER MODERATE STRAIN RATE CONDITIONS - Tomáš Doktor; Petr Zlámal; Jan Šleichrt; Tomáš Fíla; Daniel Kytýř (Acta Polytechnica CTU Proceedings, 2018)
An experimental study on energy absorption capabilities and strain rate sensitivity of ordnance gelatine was performed. Strain energy density under quasi static compression and moderate strain rate impact tests was compared. In the study two types of material were tested, bulk ordnance gelatine and polymeric open-cell meshwork filled with ordnance gelatine. From the results a significant strain-rate effect was observed in terms of ultimate compressive strength and strain energy density. In comparison of the deformation behaviour under quasi static conditions and drop weight test the difference was very significant, however slight increase in both strength and strain energy density was observed even between different impact energies and velocities during the impact testing. The peak acceleration was significantly reduced in polymer meshwork filled by gelatine in comparison to the bulk gelatine.